KEJADIAN DIARE PADA BAYI YANG DIBERI ASI EKSKLUSIF DAN NON ASI EKSKLUSIF DI WILAYAH KERJA PUSKESMAS BAKUNASE (Studi Kasus di Wilayah Kerja Puskesmas Bakunase) - Muskanan, Poppy; Aspatria, Utma; Lada, Christina Olly; Talahatu, Anna H. (Pergizi Pangan DPD NTT, 2010)
One of the factors which have an important role to increase human resources is giving breastfeeding in the early life of a baby. Babies and children under five years old who get breastfeeding have a low risk of diarrhea compare with those who do not get breastfeeding. Based on the data from the Provincial Health Service Office of East Nusa Tenggara Timur, during January-December 2008, there are 77,741 babies got diarrhea and 16 of them died. The aim of the research is to know the probability of having diarrhea case between babies who got breastfeeding with those who did not have in Puskesmas Bakunase working area during 2009. There were 60 babies have been taken as samples which consisted of 30 babies had diarrhea case and 30 babies were not. Mother’s age, education attainment, outside home job, income, knowledge about breastfeeding, age and nutrition status of the baby were observed as variables in this research. An analytical survey with a retrospective scheme had been used in this research.